2017
DOI: 10.31234/osf.io/e2nuz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Pathological Narcissism on Interpersonal and Affective Processes in Social Interactions

Abstract: Narcissism has significant interpersonal costs, yet little research has examined behavioral and affective patterns characteristic of narcissism in naturalistic settings. Here we studied the effect of narcissistic features on the dynamic processes of interpersonal behavior and affect in daily life. We used interpersonal theory to generate transactional models of social interaction (i.e., linkages among perceptions of others' behavior, affect, and one's own behavior) predicted to be characteristic of narcissism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 17 publications
1
45
0
1
Order By: Relevance
“…Clinical theory and research in related domains (e.g., borderline personality pathology) both indicate that any observed variability is likely the result of the individual attempting to regulate self, affect, and their interpersonal field [52]. For example, Wright and colleagues [24] showed that the higher a patient's NPD features, the more likely they were to respond to perceptions of dominance when interacting with another person with negative affect and quarrelsome behavior; the negative affect served as a mediator between perceptions of dominance and quarrelsome behavior. This suggests that perceiving another as asserting their dominance or taking control triggers individuals high in NPD features, resulting in dysregulated affect and ultimately hostile behavior.…”
Section: Moving Forward: Studying Dynamic Within-person Processesmentioning
confidence: 99%
“…Clinical theory and research in related domains (e.g., borderline personality pathology) both indicate that any observed variability is likely the result of the individual attempting to regulate self, affect, and their interpersonal field [52]. For example, Wright and colleagues [24] showed that the higher a patient's NPD features, the more likely they were to respond to perceptions of dominance when interacting with another person with negative affect and quarrelsome behavior; the negative affect served as a mediator between perceptions of dominance and quarrelsome behavior. This suggests that perceiving another as asserting their dominance or taking control triggers individuals high in NPD features, resulting in dysregulated affect and ultimately hostile behavior.…”
Section: Moving Forward: Studying Dynamic Within-person Processesmentioning
confidence: 99%
“…Such work has yielded results that highlight the importance of contextual factors and the interpersonal behavior of one's interactants (Pincus et al, 2014;Thomas et al, 2014b;Wright et al, 2017;Zuroff et al, 2007).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Momentary variability in anxiety was associated with greater variability in momentary hostile aggression (Edmondson et al, 2013). Among individuals with pathological levels of borderline personality disorder and narcissism traits, momentary within-participant fluctuations in negative affect predicted greater momentary aggression (Scott et al, 2017;Wright et al, 2017). Across these sources of evidence, there is ample reason to expect that greater affective variability is linked to greater aggression.…”
Section: Daily Diary and Momentary Assessment Studies Of Affect Variamentioning
confidence: 99%